2011
DOI: 10.18632/aging.100242
|View full text |Cite
|
Sign up to set email alerts
|

Health and function of participants in the Long Life Family Study: A comparison with other cohorts

Abstract: Individuals from families recruited for the Long Life Family Study (LLFS) (n= 4559) were examined and compared to individuals from other cohorts to determine whether the recruitment targeting longevity resulted in a cohort of individuals with better health and function. Other cohorts with similar data included the Cardiovascular Health Study, the Framingham Heart Study, and the New England Centenarian Study. Diabetes, chronic pulmonary disease and peripheral artery disease tended to be less common in LLFS prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
224
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(231 citation statements)
references
References 24 publications
6
224
1
Order By: Relevance
“…A stronger trend was seen with the objective physical function measures, which may be more sensitive to early physical function decline in high functioning adults . These results are consistent with conclusions described by Newman and colleagues indicating that continuous measures of physical function, like gait speed, may be sensitive for detecting "rate of aging" and early signs of future disability (Newman et al 2011). Closer examination of the objective measures showed that age adjusted mean performance for both groups was in the normal range reported in our and other studies indicating the overall high functional status of our cohort (Guralnik et al 2000;Oh-Park et al 2010;Oh-Park et al 2011;Springer et al 2007).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A stronger trend was seen with the objective physical function measures, which may be more sensitive to early physical function decline in high functioning adults . These results are consistent with conclusions described by Newman and colleagues indicating that continuous measures of physical function, like gait speed, may be sensitive for detecting "rate of aging" and early signs of future disability (Newman et al 2011). Closer examination of the objective measures showed that age adjusted mean performance for both groups was in the normal range reported in our and other studies indicating the overall high functional status of our cohort (Guralnik et al 2000;Oh-Park et al 2010;Oh-Park et al 2011;Springer et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Good physical function is rated highly among attributes of successful aging in surveys of the general elderly population (Bowling and Dieppe 2005;Rowe and Kahn 1998). Emerging evidence from human and animal studies shows that genetics partially determine exceptional longevity, and associated successful aging phenotypes (Adams et al 2008;Barzilai et al 2006;Barzilai et al 2003;Murabito et al 2012;Newman et al 2011). Offspring of parents with exceptional longevity (OPEL) who are more likely to carry longevity-associated genotypes may age more successfully than offspring of parents with usual survival (OPUS) (Barzilai et al 2006;Barzilai et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the ageing process is plastic and the accumulation of molecular damage and cell dysfunction can be slowed (8). Models of healthy ageing have been based on Rowe and Kahn's 1987 proposal which differentiated between healthy older individuals and those with disease and/or disability (6).…”
Section: Models Of Healthy Ageingmentioning
confidence: 99%
“…4 The key to extreme human longevity is believed to be a mix of genetics and environmental factors such as healthy habits and dietary patterns. [5][6][7] Aging research recently uncovered many of the molecular pathways involved in organism life span [including growth factors (i.e. insulin, IGF-1 and others), enzymes (i.e.…”
Section: Introductionmentioning
confidence: 99%